The recent Asian elephant range expansion in Yunnan, China, is associated with climate change and enforced protection efforts in human-dominated landscapes - Bai, Defeng; Wan, Xinru; Zhang, Li; Campos-Arceiz, Ahimsa; Wei, Fuwen; Zhang, Zhibin (Frontiers in Ecology and Evolution, 2022)
Recently, the northward movement of Asian elephants (Elephas maximus) in Yunnan, China has caused worldwide attention. Climate change or human disturbances have been proposed to be the key drivers, but these hypotheses have not been rigorously tested. In this study, we quantified associations of climate change and human impacts with the recent range expansion of Asian elephants in southwest China. We found that the first observation probability of this species in a new place during 1959–2021 had a significant and positive association with change of air temperature and human density, resulting in a movement towards a high-latitude region with warmer climate and higher human density; however, its association with precipitation was scale-dependent in time: positive or negative during the past 10 or 5 years, respectively. Under the enforced policy of protection, human-dominated areas became preferred habitats for elephants. Our results indicate that climate change and enforced protection efforts in human-dominated landscapes in the last few decades are important drivers for the recent range expansion of Asian elephants in Yunnan, China. It is necessary to expand the current protected areas or habitat corridors toward the north, or to set up new reserves in the north, and to set up barriers between human settlements and elephant habitats for facilitating elephant movements and minimizing human-elephant conflicts under the accelerated global change.